Recruitment of entomopathogenic nematodes by insect-damaged maize roots - Rasmann, Sergio; Köllner, Tobias G.; Degenhardt, Jörg; Hiltpold, Ivan; Toepfer, Stefan; Kuhlmann, Ulrich; Gershenzon, Jonathan; Turlings, Ted (My University, 2005)
Plants under attack by arthropod herbivores often emit volatile compounds from their leaves that attract natural enemies of the herbivores. Here we report the first identification of an insect-induced belowground plant signal, (E)-β-caryophyllene, which strongly attracts an entomopathogenic nematode. Maize roots release this sesquiterpene in response to feeding by larvae of the beetle Diabrotica virgifera virgifera, a maize pest that is currently invading Europe. Most North American maize lines do not release (E)-β-caryophyllene, whereas European lines and the wild maize ancestor, teosinte, readily do so in response to D. v. virgifera attack. This difference was consistent with striking differences in the attractiveness of representative lines in the laboratory. Field experiments showed a fivefold higher nematode infection rate of D. v. virgifera larvae on a maize variety that produces the signal than on a variety that does not, whereas spiking the soil near the latter variety with authentic (E)-β-caryophyllene decreased the emergence of adult D. v. virgifera to less than half. North American maize lines must have lost the signal during the breeding process. Development of new varieties that release the attractant in adequate amounts should help enhance the efficacy of nematodes as biological control agents against root pests like D. v. virgifera.